A narrative inquiry into lecturers’ experiences with standardized testing pressures in an Indonesian English Language Education Department - I Putu Andre Suhardiana; I Gusti Ayu Indah Triana Juliari; Made Wahyu Mahendra; Astuti Wijayanti (Universitas Islam Sultan Agung, 2026)
Indonesia’s English Language Education Departments have two priorities: developing students’ communicative competence and ensuring that students are able to graduate with a TOEFL test score. Such conditions create a form of ‘washback’ where testing priorities are at odds with the principles of communicative language teaching, shaping the approach to teaching. Negative washback has been documented; however, few qualitative studies examine the internal tensions, lived experiences, and emotional struggles of lecturers. This study examines how Indonesian ELED lecturers negotiate the conflict between their CLT philosophy and the demands of standardized testing. A narrative inquiry was conducted with seven lecturers from an Indonesian public university ELED. Data from semi-structured interviews were analyzed using a three-dimensional framework (temporality, sociality, place) to construct and interpret participants’ experiential narratives. Lecturers face a conflict in which they differentiate themselves as either a Teacher or a Test Preparer. To protect their pedagogical values, they practice ‘quiet resistance,’ whereby test practice is incorporated into communicative tasks. While this is a form of active resistance, the emotional costs are significant, leading to feelings of guilt, fatigue, and cynicism. The conflict is pedagogical, personal, and continual, leading to the fragmentation of professional identity and the erosion of psychosocial well-being. Lecturers show resilient agency through covert negotiation; yet, the misalignment between assessment policies and the communicative goals of teaching remains unaddressed, with implications for the sustainability of educators. This study recommends a re-evaluation of assessment policies to align with pedagogical values and lecturer well-being support within institutional frameworks.